Corporate psychopaths in Australian workplaces : their influence on organisational outcomes - Boddy, Clive R. (Curtin University, 2009)
This thesis describes the construct of psychopathy and the study of psychopaths. It identifies that psychopaths have been studied extensively in their criminal manifestations but that there is a large and recognised gap in the literature and a stated need for the study of successful psychopaths and Corporate Psychopaths. The thesis outlines the research instrument used to identify such people in a 2008 survey of management behaviour among 346 managers in Australia. The robust statistical validity and reliability of the instrument is described, and the high level of face validity of the resultant findings is noted. The research defined Corporate Psychopaths as psychopaths who work in corporations. Operationally, Corporate Psychopaths were defined as those managers who scored above 12 on a psychopathy measure of their behaviour. It investigated outcomes in terms of the influence of the presence of Corporate Psychopaths on organisational constraints, withdrawal from the workplace, workplace conflict and bullying, workload, levels of job satisfaction and perceived levels of corporate social responsibility.Nearly all of the dependent variables deployed in the current research show a significant relationship with Corporate Psychopaths in the expected direction. Findings highlight that while Corporate Psychopaths comprise only a small minority of employees and managers, they have a significant, negative influence on organisational outcomes. Corporate Psychopaths create disorder in the workplace on a scale previously unimagined and unidentified until now. They directly or indirectly account for large amounts of rudeness and bullying and significant amounts of other types of employee-related work difficulties. They also have a strongly negative influence on a whole host of workplace outcomes, including withdrawal from the workplace, workplace constraints and job satisfaction.The presence of Corporate Psychopaths in organisations thus costs organisations in lost employee time as they withdraw from the organisational environment and in sub-optimal employee performance as they cope with extra organisational constraints. The presence of Corporate Psychopaths in organisations presents unnecessarily difficult working conditions for employees as they cope with a hostile working environment and with myriad negative influences associated with poor levels of job satisfaction. This has practical implications for organisational and human resource management as discussed in the thesis.